1964
DOI: 10.1128/jb.87.4.920-923.1964
|View full text |Cite
|
Sign up to set email alerts
|

INDUCTION OF THE METHIONINE-ACTIVATING ENZYME IN SACCHAROMYCES CEREVISIAE

Abstract: Induction of the methionine-activating enzyme in Saccharomyces cerevisiae. J. Bacteriol. 87:920-923. 1964.-The methionine-activating enzyme was induced in yeast in the presence of methionine, resulting in an accumulation of S-adenosylmethionine. Formation of the sulfonium derivative prevented the accumulation of high levels of free methionine in induced cells. The physiological significance of this phenomenon is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

1964
1964
1973
1973

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The enzyme has been monitored in a variety of microorganisms (8,17,21), as well as in liver extracts (6,18). Under certain conditions, methionine adenosyltransferase from yeast has been shown to be induced in the presence of low concentrations of methionine (20).…”
mentioning
confidence: 99%
“…The enzyme has been monitored in a variety of microorganisms (8,17,21), as well as in liver extracts (6,18). Under certain conditions, methionine adenosyltransferase from yeast has been shown to be induced in the presence of low concentrations of methionine (20).…”
mentioning
confidence: 99%
“…Adenosylmethionine synthesis and turnover. Since methionine stimulates the formation of S-adenosylmethionine in S. cerevisiae (7,9), yet does not adversely affect the sai-1 strains, it was suggested that the mutants may employ a mechanism which limits the rate of S-adenosylmethionine synthesis, or in some other manner limits the accumulation of this compound, thereby avoiding self-inhibition. It was also possible that the sai-1 mutants might resist the effects of S-adenosylmethionine synthesized intracellularly by depositing it in the vacuole, as previously described (8,16,17).…”
Section: Resultsmentioning
confidence: 99%
“…We have been unable to distinguish sai-1 strains from wild-type strains on the basis of growth in the presence of methionine alone even under conditions where the external methionine concentration was as much as 10 times higher than the concentrations reported here. One would expect an increase in the concentration of S-adenosylmethionine when the level of extracellular methionine is increased (7)(8)(9). The possibility that the externally supplied and internally synthesized S-adenosylmethionine are physically separated and participate in different reactions cannot be excluded at this time.…”
Section: Resultsmentioning
confidence: 99%
“…Methionine is accumulated in the sensitive strain. The measurement of accumulated methionine is complicated by the cellular conversion of the amino acid to S-adenosyl-methionine (Schlenk and De Palma, 1957; Pigg, Sorsoli, and Parks, 1964). The sulfonium derivative would not be assayed by the microbiological technique (Pigg, Spence, and Parks, 1962).…”
Section: Resultsmentioning
confidence: 99%